PENERAPAN MANAJEMEN RISIKO PADA PENGELOLAAN PROPERTY SYARIAH : Studi Pada PT. Granada Property Syariah Kab. Konawe Selatan Provinsi Sulawesi Tenggara - Baharuddin, Kurniawan Harminsyah; Suprayitno, Nur Fadillah; Sari, Annisa; Trimuliani, Diva (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2025)
This study aims to examine the implementation of risk management in the management of sharia-compliant property at PT Granada Property Syariah in South Konawe Regency, Southeast Sulawesi Province. The focus of the study is directed at how the company identifies, manages, and anticipates various forms of risk without the involvement of banking institutions, in accordance with the principles of Islamic muamalah which reject usury. This study uses a qualitative method with an interpretive case study approach, which aims to explore in-depth the mechanisms and strategies of risk management from a social and religious perspective. The results show that Granada Property Syariah implements three main transaction forms: cash sales, soft cash sales, and sharia-compliant credit sales. The success of the implemented risk management system is supported by the principles of transparency, fairness, and trustworthiness. This study contributes to strengthening the concept of sharia-compliant risk management by providing empirical evidence of the implementation of non-bank systems in the property business. In addition, the results emphasize the importance of risk management based on Islamic values ​​to maintain business continuity and strengthen public trust in sharia-compliant economic practices.